Application of the CERT values measurement model for organizational culture in the Management And Quality company - Cárdenas Jiménez, Santiago; Calderón Narváez, Abigail; Rodríguez Ríos, Claudia Yadira (Escuela Colombian de Ingeniería, 2023)
At present, it has been shown that very few SMEs have knowledge of the Business Process Management BPM system, which offers a series of strategies and benefits oriented towards processes, using technology systems in terms of information management, evaluating the organizational culture and covering all the operational and business processes of the organization, in order to increase productivity and competi tiveness, guaranteeing continuous improvement of internal processes following their life cycle, where they are documented, analyzed, improved , are implemented, and are monitored and controlled. In this study, the BPM culture of an information technology SME, called Man agement and Quality, was evaluated based on the study carried out by Jan Vom Brocke, in which 4 values are established, which are: customer orientation, excel lence, responsibility, and teamwork, called CERT values, the survey adapted to the context of the company and Colombia was applied; As a result, opportunities for improvement in excellence were found represented by the dimensions of contin uous improvement and innovation, and in the formal structures, dimension of teamwork, recommendations were made for these findings.

En la actualidad, se ha demostrado que muy pocas PYMES tienen conocimiento de la Sistema BPM Business Process Management, que ofrece una serie de estrategias y beneficios orientados a procesos, utilizando sistemas tecnológicos en materia de información gestión, evaluando la cultura organizacional y cubriendo todos los aspectos operativos y procesos de negocio de la organización, con el fin de incrementar la productividad y competitividad, garantizando la mejora continua de los procesos internos siguiendo su ciclo de vida, donde se documentan, analizan, mejoran, se implementan y se supervisado y controlado. En este estudio se evaluó la cultura BPM de una PYME de tecnologías de la información, denominada Gestión y Calidad, en base al estudio realizado por Jan Vom Brocke, en el que se establecen 4 valores que son: orientación al cliente, excelencia, responsabilidad y trabajo en equipo, denominados valores CERT, la encuesta adaptada a la se aplicó contexto de la empresa y Colombia; Como resultado, las oportunidades para la mejora en la excelencia se encontraron representadas por las dimensiones de mejora continua e innovación, y en las estructuras formales, la dimensión de trabajo en equipo, se realizaron recomendaciones para estos hallazgos.
Keywords: Negocios -- Administración Industrial -- Pymes; Cultura Organizacional -- Pymes; Tecnologías de Información -- Pymes; Negocios -- Administración Industrial -- Pymes; Cultura Organizacional -- Pymes; Tecnologías de Información -- Pymes; Business -- Industrial Administration -- SMES; Organizational Culture -- SMES; Information Technologies -- SMES